Paraprofessional Educator Manager A New Professional Role in Early Childhood Education - Zehrbach, R. Reid.; Illinois Univ., Urbana. Inst. of Research for Exceptional Children ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
Described is the development of the Paraprofessional Educator Manager (PEM) Model and the role of the PEM in early childhood education. Various studies are first cited to show that individuals other than trained teachers can stimulate the intellectual development of preschool children. The PEM model is thought to provide for the greatest integration of positively oriented activities at home and at school at the lowest cost possible. The model is also said to provide a training ground for the upgrading of adults as well as children. The PEM is explained to supervise paraprofessional teacher aides and paraprofessional home visitors who attempt to coordinate the classroom and home learning environments. The role of the PEM is shown to require him to retrain, plan, organize, supervise, and integrate the activities of eight paraprofessionals working with 48 children and their families. Implementation of the model and training of the PEM are then briefly noted. (CB)
Sponsoring Agency: Office of Education (DHEW), Washington, DC. Bureau of Research.
Contract Number: OEC-6-10-235.
Educational level discussed: Early Childhood Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrative Policy; Administrator Role; Early Childhood Education; Educational Programs; Models; Nonprofessional Personnel; Teacher Aides; Teacher Supervision